Characterization of the urogenital microbiome in patients with urinary tract infections - Fitri Nadifah; Wayan Tunas Artama; Budi Setiadi Daryono; Endah Retnaningrum (Indonesian Journal of Biotechnology, 2022)
Standard microbiological culture techniques can only identify a fraction of the urogenital microbiome. Meanwhile, identifying and characterizing infectious microorganisms are very important for the success of diagnosis and treatments, especially for Urinary Tract Infection (UTI) patients. This study aimed to characterize the urogenital microbiome of UTI patients using 16S rRNA gene sequencing. We sequenced two pooled DNA samples from voided urine of UTI patients (21 females and 13 males). To determine the structure and composition of taxa in the samples, 16S rRNA gene sequencing was performed using the Illumina Mi‐Seq paired‐end platform. The most abundant genera were Burkholderia‐Caballeronia‐Paraburkholderia (71%) followed by Prevotella (33%), Escherichia‐Shigella (24%), Klebsiella (23%) and Sneathia (10%). The female microbiome was dominated by Prevotella bivia (28%), Escherichia coli (24%), Sneathia sanguinegens (7%) and Klebsiella pneumoniae (4%). On the other hand, the male microbiome was dominated by K. pneumoniae (23%) and E. coli (2%). K. pneumoniae and E. coli were the most abundant species found in both microbiomes. The 16S rRNA gene sequencing used in this study successfully uncovered the composition of the urogenital microbiome, which might not have been possible with conventional culture methods.